Patent inventions--intellectual property and the Victorian novel - Pettitt, Clare (Oxford University Press, 2004)
This volume suggests that the fierce debates over patent law and the discussion of invention and inventors in popular texts during the 19th century informed the parallel debate over the professional status of authors.